Impact of Placenta Previa on Neonatal and Maternal Health - Sumeeta; Ali, Sania; Gul, Shumail; Mal, Huna Gangu; Sakeena; Fatima, Aryan; Raishem (Indus Journal of Bioscience Research, 2025)
Background: Placenta previa, increasingly linked to prior caesarean section, is a major driver of peripartum haemorrhage, transfusion and hysterectomy, with downstream neonatal risks from prematurity and intensive care. Objective: To quantify maternal and neonatal outcomes associated with placenta previa and suspected placenta accreta spectrum (PAS), and to identify practice factors associated with morbidity in a tertiary centre, PUMHS Nawab Shah. Methods: Analytical cohort was conducted at the Department of Obstetrics & Gynaecology, PUMHS (Shaheed Benazirabad) over six months (9 Jul 2024–9 Jan 2025). We analysed 150 consecutive ultrasound-diagnosed low-lying/previa pregnancies. Data were abstracted using a standard proforma. Descriptive summarised case mix; χ²/Fisher’s exact and Mann–Whitney/Kruskal–Wallis compared groups; selected logistic models explored adjusted associations (α=0.05). Results: Complete/major previa comprised 42.0%; anterior implantation 54.0%; PAS suspected 42.7%. Median quantified blood loss was 1691 ml (IQR 1210–2050); PPH≥1000 ml 88.7%, transfusion 90.0%, hysterectomy 14.7%, ICU 18.7%. Gestational age was 35.9±1.9 weeks; preterm